Lipid droplets in central nervous system and functional profiles of brain cells containing lipid droplets in various diseases - Longxiao Zhang; Yunfei Zhou; Zhongbo Yang; Liangchao Jiang; Xinyang Yan; Wenkai Zhu; Yi Shen; Bolong Wang; Jiaxi Li; Jinning Song (Journal of Neuroinflammation)
Abstract Lipid droplets (LDs), serving as the convergence point of energy metabolism and multiple signaling pathways, have garnered increasing attention in recent years. Different cell types within the central nervous system (CNS) can regulate energy metabolism to generate or degrade LDs in response to diverse pathological stimuli. This article provides a comprehensive review on the composition of LDs in CNS, their generation and degradation processes, their interaction mechanisms with mitochondria, the distribution among different cell types, and the roles played by these cells—particularly microglia and astrocytes—in various prevalent neurological disorders. Additionally, we also emphasize the paradoxical role of LDs in post-cerebral ischemia inflammation and explore potential underlying mechanisms, aiming to identify novel therapeutic targets for this disease.